ANALISIS KINERJA PELAYANAN PADA SAMSAT DAERAH SURABAYA UTARA - Romy, Robby Aditiya; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the performance of public service at SAMSAT North Surabaya. The research is conducted at SAMSAT North Surabaya is the public service institution which provides service to the public fast, easy, and transparents. This research has been carried out by using qualitative descriptive. The information determination technique has been done by performing purposive sampling because this research tries to seek deep information from people who knows the focus of the research very well. of this research shows that the performance of SAMSAT North Surabaya has been running properly according to the indicators which have been stated in the Regulation of Minister of the Empowerment of State Apparatus No. 001 of 2015 which relates to the guidelines of public service performance analysis includes public service standard which has been carried out well according to the existing regulation, intimation services has been formulated properly according to the main tasks of the organization, public satisfaction survey has been conducted periodically in 3-month periods, complaints management has been established to find out the complaints of taxpayers in order to be solved soon, and public service information system has been determined and implemented in accordance with the existing regulations.Keywords: Analysis, Performance, Public Service